2004
DOI: 10.1128/jcm.42.8.3844-3846.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Spread of emm Type 28 Isolates of Streptococcus pyogenes That Are Multiresistant to Antibiotics

Abstract: Fifty-three pharyngitis-related and invasive isolates of Streptococcus pyogenes that are resistant to bacitracin were collected. They were also resistant to streptomycin, kanamycin, macrolides, lincosamides, and streptogramin B. These multiresistant isolates were of emm type 28 and clonally related as shown by pulsed-field gel electrophoresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 21 publications
(5 reference statements)
4
38
0
1
Order By: Relevance
“…Moreover, the types that are most dominant in invasive categories, and hence those responsible for the observed decrease in diversity, are almost always the same-most notably M1 and M3. 8,12,18,[32][33][34][35][36] Similar dynamics, including decreased diversity and the dominance of specific types, are apparent in studies of more specific clinical phenomena such as fatality, associated with M1, M3 and M12, 32 puerperal sepsis, associated with M28, 34,36,37 STSS, associated with M1 and M3, 12,35,38 epidemic ARF, associated with M5 and M18, 39 and geographically widespread epidemic behavior, most commonly associated with M1. 2,12 Despite genetic changes in these serotypes over time, including alterations of virulence and antibiotic resistance factors, these associations generally remain stable.…”
Section: Clinical Relevance Of M Typementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the types that are most dominant in invasive categories, and hence those responsible for the observed decrease in diversity, are almost always the same-most notably M1 and M3. 8,12,18,[32][33][34][35][36] Similar dynamics, including decreased diversity and the dominance of specific types, are apparent in studies of more specific clinical phenomena such as fatality, associated with M1, M3 and M12, 32 puerperal sepsis, associated with M28, 34,36,37 STSS, associated with M1 and M3, 12,35,38 epidemic ARF, associated with M5 and M18, 39 and geographically widespread epidemic behavior, most commonly associated with M1. 2,12 Despite genetic changes in these serotypes over time, including alterations of virulence and antibiotic resistance factors, these associations generally remain stable.…”
Section: Clinical Relevance Of M Typementioning
confidence: 99%
“…Another example of tight correlation between rare antibiotic resistance phenotypes and specific M types comes from a study in France which showed a unique resistance to bacitracin (paired with wide resistance to other diverse antibiotics) among M28 isolates. 37 Another study showed that isolates of a variety of M types collected from apparently hospital acquired GAS infections (HAI GAS) expressed more (and more diverse) antibiotic resistance phenotypes than non-hospital acquired strains, and those strains tended to express resistance phenotypes not otherwise associated with their M types. 21 The number of HAI GAS strains studied was very small, but the results were suggestive of antibiotic resistance element transfer in the hospital environment.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 2 more Smart Citations
“…European clone lineage (Mihaila-Amrouche et al, 2004). Although not very common amongst streptococci (Malhotra-Kumar et al, 2005), efflux pumps also confer tetracycline resistance, and one such element was detected in isolate JI7.…”
Section: Antimicrobial Resistancementioning
confidence: 99%